Design and Optimization of Inductively Coupled Spiral Square Coils for Bio-Implantable Micro-System Device - Abdelghani Lakhdari; Nasr-Eddine Mekkakia Maaza; Meriem Dekmous (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Due to the development of biomedical microsystems technologies, the use of wireless power transfer systems in biomedical application has become very largely used for powering the implanted devices. The wireless power transfer by inductive resonance coupling link, is a technic for powering implantable medical devices (IMDs) between the external and implanted circuits. In this paper we describe the design of an inductive resonance coupling link using for powering small bio-implanted devices such as implantable bio-microsystem, peacemaker and cochlear implants. We present the reduced design and an optimization of small size obtained spiral coils of a 9.5 mm2 implantable device with an operating frequency of 13.56 MHz according to the industrial scientific-medical (ISM). The model of the inductive coupling link based on spiral square coils design is developed using the theoretical analysis and optimization geometry of an inductive link. For a mutual distance between the two coils at 10mm, the power transfer efficiency is about 79% with , coupling coefficient of 0.075 and a mutual inductance value of 2µH. In comparison with previous works, the results obtained in this work showed better performance such as the weak inter coils distance, the hight efficiency power transfer and geometry.